The smoking rate and its repercussions on an asthmatic population sample - Seabra,Bárbara (2008)
Setting - The smoking rate in Portugal is 19.2% and 33% in Europe. There is no precise data on the smoking rate of the asthmatic population. Aim - To determine the smoking rate and its repercussions on an asthmatic population sample. Design - One hundred and ten asthmatic patients observed in asthma consultations were classified as non-smokers, former-smokers or smokers. Subsequently, based on functional and clinical criteria, they were classified as having Severe Persistent (SPA), Moderate Persistent (MoPA), Mild Persistent (MiPA) and Intermittent (IA) Asthma. Results - 8% of 110 patients (65% female) aged 18 to 78 years were smokers, 9% former-smokers, 83% non-smokers. Among the asthmatics: - smokers: 0% SPA, 56% MoPA, 33% MiPA, 11% IA; - former smokers: 10% SPA, 30%MoPA, 50% MiPA, 10% IA; - non-smokers: 7% SPA, 27% MoPA, 36% MiPA, 30% IA. Patients with exposure to smoking had worse functional evaluation than those without exposure. Conclusion - In this population sample the rate of current smoking habits (8% of current smokers) was considerably low than in Portugal (19.2%). Analysis and comparison of asthma severity and functional evaluation detected worse results in both current and former smokers. These reinforce the role of tobacco exposure in asthma aggravation and worsening of its prognosis. Further studies may be important to prove and alert the asthmatic population, in particular, to the well-known risks of smoking.